The role of emotion regulation between cognitive distortion and stress in parenting children with developmental disorders - Rahayu, Esthi -; Puji Sugiharto, Dwi Yuwono; Purwanto, Edy -; Awalya, Awalya - (Jurnal Psikologi, 2026)
Background: Parenting stress is often discussed in research on parenting children with developmental disorders. According to cognitive behavioral theory, cognition influences behavior. To clarify the dynamics of the relationship between cognitive distortion and parenting stress, emotional regulation is placed as a mediator variable.Purpose: This study aims to determine the relationship between cognitive distortion, emotional regulation and parenting stress in mothers who care for children with developmental disorders.Method: The characteristics of the research participants are mothers who raise children with developmental disorders. There are 91 mothers who filled out the Parenting Stress Scale, Emotional Regulation Scale and Cognitive Distortion Scale of Parenting. Data analysis using SPSS through PROCESS model 4.Findings: The results of the mediation test in this study indicate that emotional regulation does not act as a variable that mediates cognitive distortion with parenting stress. The correlation between cognitive distortion and parenting stress is positive and very significant (p <0.01), the correlation between emotional regulation and parenting stress is negative and significant (p <0.05); but the negative correlation between cognitive distortion and emotional regulation is not significant (p>0.05).Implication: Emotional regulation is not a mediator but a predictor and also a moderator..